Total hemocyte and hemoglobin changes in nypa palm worm (Namalycastis rhodochorde) to Aeromonas sp. NrBF9 infection - ARI HEPI YANTI; HERALDUS I. ARINENDO; TRI RIMA SETYAWATI; RIKHSAN KURNIATUHADI (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Yanti AH, Arinendo HI, Setyawati TR, Kurniatuhadi R. 2025. Total hemocyte and hemoglobin changes in nypa palm worm (Namalycastis rhodochorde) to Aeromonas sp. NrBF9 infection. Biodiversitas 26: 4274-4283. Nypa palm worms (Namalycastis rhodochorde) are polychaetes essential to mangrove ecosystems as detritivores and decomposers. They also hold economic value for coastal communities through cultivation. However, pathogenic infections threaten their survival and aquaculture. Aeromonas sp. NrBF9, isolated from the worms’ fecal pellets, is an indigenous pathogen with hemolytic and DNase activities that likely cause hematological damage. Previous studies observed blanching symptoms in cultured worms exposed to Aeromonas from their feces, hypothesized to result from blood and hemocyte damage, though this remains unconfirmed. This study examined the hematological profile of nypa palm worms after dorsal injection with Aeromonas sp. NrBF9 at 10³, 10?, and 10? cells/mL. Parameters assessed included total hemocyte counts, hemoglobin levels, and hemocyte diameters. Hemolytic activity was tested using a smear method on worm blood agar. Results showed infected worms developed anemia, with significant reductions in total hemocyte counts (32.9%, 39.2%, and 39.9% decreases at 10³, 10?, and 10? cells/mL, respectively; p = 0.007, p<0.05), and hemocyte diameters (8.8%, 12.5%, and 15.0% decreases at 10³, 10?, and 10? cells/mL, respectively; p = 0.00, p<0.05). Infected worms also exhibited paler hemocytes and hemocyte aggregation, while hemoglobin levels remained unchanged (p = 0.679, p>0.05). Aeromonas sp. NrBF9 displayed ?-hemolytic activity on worm blood agar. These findings show changes in hemocyte counts and colonization caused by Aeromonas infection, emphasizing the need for early detection and management to minimize losses and boost nypa palm worm aquaculture productivity.